Modes of Governance and Local Economic Development: An Integrated Framework for Comparative Analysis of the Globalizing Cities of India. (November 2017) - Chatterji, Tathagata
This article explores how variations in provincial-state and city-level political cultures influence urban economic trajectory by mediating forces emerging out of global economic demand and a uniform national regulatory regime. The research shows how an integrated urban governance framework designed to analyze and compare governance modes of advanced capitalist cities through a fixed set of criteria (e.g., governing relations, governing logic, key decision makers, and political objectives) could be recalibrated through inclusion of additional parameters (e.g., local political culture and scalar location of power) so as to expand its applicability to an emerging economy, such as India, having a large, mostly poor, rural population and a high degree of internal sociocultural diversity. Competition between India's regional elites to attract global information technology (IT)-enabled "business process outsourcing" economy investments, through land-use conversion of farmlands at the outer periphery of the metropolitan regions, forms the backdrop of the research.